Research anthology on usage, identity, and impact of social media on society and culture (Information Science Reference, 2022)
"This reference set discusses the impact social media has on an individuals' identity formation as well as its usage within society and cultures, exploring new research methodologies and findings into the behavior of users on social media as well as the effects of social media on society and culture as a whole"--